Audiological, Phonatory and Cardiac Correlates of Individuals Exposed to Low-Frequency Noise or at Risk of Vibroacoustic Disease - Verma, Himanshu; Shah, Jyoti; Singh, Apurva; Singh, Shakshi; Sharma, Bhawna; Shukla, Bhanu (International Archives of Otorhinolaryngology, 2023)
Introduction Low-frequency noise (LFN) is hazardous to hearing. Long-term exposure to LFN may lead to vibroacoustic disease (VAD), which not only affects a specific organ but the physiological function of entire systems, such as the auditory, phonatory, respiratory, and cardiac systems. Moreover, VAD may lead to many psychological problems and hence affect the quality of life. Objective To investigate the adverse effects of LFN on hearing, acoustic and perceptual correlates of the voice, blood pressure, cardiac rate, and anxiety level. Method A total of 20 subjects exposed to LFN and 20 not exposed to LFN were included, and a detailed case history was recorded. The patients were submitted to pure tone audiometry, otoscopic examination, acoustic and perceptual analyses of the voice, maximum phonation time, and an assessment of the s/z ratio. We also assessed blood pressure, and the results of a voice-related quality of life questionnaire and of the Hamilton anxiety rating scale. Results The results indicate that LFN had an adverse impact on the high-frequency threshold. The present study found a significant difference in shimmer and harmonics-to-noise ratio (HNR) values. Few subjects had high blood pressure and showed the sign of anxiety on the Hamilton anxiety rating scale. Conclusion Low-frequency noise has adverse effects on entire systems of the body and causes many psychological issues, which, in turn negatively affect quality of life.